Brief Clinical Report: Hypophosphatasia—Diagnostic Considerations and Treatment Outcomes in an Infant - Sara Duffus; Bradly Thrasher; Ali S. Calikoglu (Case Reports in Pediatrics)
Hypophosphatasia (HPP) is a rare, inherited metabolic bone disorder characterized by low serum alkaline phosphatase activity and impaired bone mineralization. Clinical manifestations and severity of symptoms vary widely in HPP, ranging from in utero death to isolated dental manifestations in adults. Treatment with enzyme replacement therapy has been reported to improve outcomes in perinatal, infantile, and childhood forms of HPP. Here, we present a case of a boy with poor linear growth, mild limb bowing, and radiographic rickets who was diagnosed with HPP before 6 months of age. Treatment with enzyme replacement therapy was initiated at 7 months of age, after which significant improvements in radiographic findings and linear growth were demonstrated. This case highlights several important challenges in the diagnosis, classification, and management of HPP.